(untitled) (Ciudades, 2017)
The disappearance of reformist culture with the rising of neoliberal politics that proclaim the “public” removal is based on the globalisation of financial economy. This economy’s practice and theoretical schemes leave no place for citizens’ culture and town. Recent budget cuts and privatizations constitute a threat for Keynesian “welfare state”, whose link to the Fordist production mode in extinction almost turns this state into an anachronism. The collective action prevails in order to promote a progressive direction towards a fair and emancipated society, an “urban” utopia, which is opposed to the capital changing scenarios and its challenges of accumulation. The financial dynamics, the reformism itself, and also the idea of civilization and its icons should be criticised.